2011
DOI: 10.1681/asn.2010040423
|View full text |Cite
|
Sign up to set email alerts
|

Epac-Rap Signaling Reduces Cellular Stress and Ischemia-induced Kidney Failure

Abstract: Renal ischemia-reperfusion injury is associated with the loss of tubular epithelial cell-cell and cell-matrix interactions which contribute to renal failure. The Epac-Rap signaling pathway is a potent regulator of cell-cell and cell-matrix adhesion. The cyclic AMP analogue 8-pCPT-2Ј-O-Me-cAMP has been shown to selectively activate Epac, whereas the addition of an acetoxymethyl (AM) ester to 8-pCPT-2Ј-O-MecAMP enhanced in vitro cellular uptake. Here we demonstrate that pharmacological activation of Epac-Rap sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 39 publications
2
48
0
Order By: Relevance
“…We previously established that 8-pCPT-29-O-Me-cAMP-AM selectively activates Epac, whereas forskolin induces activation of Epac as well as protein kinase A (PKA). 10,11 The effect of long-term activation of PKA by forskolin may antagonize the protective outcome we observed in the acute exposures in monolayer assays and reflect PKAmediated differences in gene expression.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…We previously established that 8-pCPT-29-O-Me-cAMP-AM selectively activates Epac, whereas forskolin induces activation of Epac as well as protein kinase A (PKA). 10,11 The effect of long-term activation of PKA by forskolin may antagonize the protective outcome we observed in the acute exposures in monolayer assays and reflect PKAmediated differences in gene expression.…”
Section: Discussionmentioning
confidence: 95%
“…In our previous studies, we demonstrated that pharmacologic activation of Epac-Rap signaling provides protection against cell detachment during IR injury 10 and apoptosis during exposure to cisplatin. 11 Because excessive generation of ROS by mitochondria is a common feature in a diverse array of renal pathologies including IR injury and cisplatin nephrotoxicity, we hypothesized that Epac-Rap signaling influences mitochondrial function during injury.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations